Track Record and Research Challenges of Automotive Vocational Lecturer in Indonesia: Screening from Google Scholar 2016-2018 - Bagiyo Condro Purnomo; Muhammad Latifur Rochman; Muji Setiyo (LP2M - Institut Teknologi Padang, 2019)
This article presents a research review of automotive vocational lecturers in Indonesia obtained from Google Scholar during 2016-2018. We found more than 500 articles on Google Scholar produced by 277 lecturers from automotive vocational programs. However, through data filtering, there are only 208 publications related to automotive, including the development of learning media in VHE. Looking at the world automotive research trend (which leads to major issues regarding battery systems, downsizing and turbocharging, and advanced combustion modes), and with concerns about the availability of fossil energy, major and fundamental reforms are needed for research activities in automotive vocational lecturers in Indonesia, both in terms of topic and depth of research material. As a recommendation, stakeholders in automotive vocational programs in universities should immediately form a research roadmap together and form a national automotive research consortium in order to contribute in realizing environmentally friendly vehicle technology and a sustainable national transportation system.